Acute Care and Treatment of Migraine. Issue 4 (December 2020) - Konstantinos, Spingos; Vikelis, Michail; Rapoport, Alan
Abstract : Objective: Migraine is a chronic neurological disease involving the brain and its vasculature, typically characterized by recurrent attacks of moderate or severe throbbing headache, accompanied by sensitivity to light and sound, and associated with nausea, vomiting, and inability to move due to worsening of pain. About 30% of migraineurs have some type of aura, most often visual. Migraine attacks, if untreated or suboptimally treated, usually result in significant disability, requiring bed rest and resulting in poor quality of life. Increased frequency of attacks and overuse of acute care medication are significant risks for chronification, resulting in the transformation of episodic migraine into chronic migraine. We aim to review most acute care treatments for migraine. Methods: Current treatment options for migraine attacks were reviewed from the selected literature and combined with our clinical experience. Results: Current acute treatment options for migraine attacks include over-the-counter analgesics, at times combined with caffeine, nonsteroidal anti-inflammatory medications, opioids, and migraine-specific medications such as triptans and ergots. In the near future, we will probably have 3 gepants (small-molecule calcitonin gene-related peptide [CGRP] receptor antagonists). The first one was just approved in the United States. A ditan acting as a stimulator of 5-HT1F receptors, was also just approved by the FDA. Stimulation of the trigeminal, vagal, occipital, and even upper arm peripheral nerves through electrical nerve stimulation devices and magnetic stimulation devices are available as alternative, nondrug treatment options. Several devices have already been FDA-allowed for treatment in the United States and/or approved elsewhere, and others will follow soon. Behavioral medicine techniques such as biofeedback training and mindfulness have been available for some time and are often helpful. Conclusion: A wide variety of acute care options to treat migraine are available, and others will soon be and will herein be described in further detail. Some medications have been approved by regulatory authorities in countries other than the United States, and some devices have been given a CE Mark in Europe.